KREATIVITAS BERFIKIR, TEKNIK PENULISAN DAN PENGUASAAN METODOLOGI PENELITIAN: Analisis Terhadap Kualitas Skripsi Mahasiswa STAIN Jurai Siwo Metro - Wahyudin, Wahyudin (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2017)
Undergraduate Thesis (Skripsi) is one of the scientific writing that should be written by the students before finishing their study at a university. It is also called scientific wrtting because it shoul be written logically, systematically and originally. For good scientific writing, the students need to the thinking creativity, writing technique, and research methodology mastery.The aim of this research is know the quality of undergraduate thesis written by the students of State Islamic College (STAIN) Jurai Siwo Metro in the period of 2010-2015. This research had been conducted in STAIN Jurai Siwo Metro Library by observing and anlysing the tudents’ undergraduate thesis that written in those periods. Based on the finding of research can be identified that the quality of students undergraduate thesis still in low level. The low quality of students’ undergraduate thesis caused by 69,60% of students had lack of thinking creativity, 64,61% of students could not write perfectly in writing technique, and 64,57% of students didn’t master the research methodology. This low quality was not only made by the students. But also there were many factors that can influence the case. The lecuters and the sponsors were also had strategis role in their writing. But more over the students should be studying hard to be able and master thinking creavity, writing technique dan research methodology.